MORFOLOGI KELENJAR PAROTIS DAN KELENJAR MANDIBULARIS SAPI SUMBA ONGOLE (Bos indicus) - Sharoniva J. Koanak; Inggrid Trinidad Maha; Filphin A. Amalo; Yulfia N. Selan (JURNAL KAJIAN VETERINER, 2019)
The sumba ongole cattles (Bos indicus) is one of local cattles in Indonesia. Oral cavity of cattle contains parotid and mandibular salivary glands, which have an important role to digesting food. This research aimed to identify the morphology of parotid and mandibular salivary glands of sumba ongole cattles. The sample were obtained from Sumba Timur slaughter house. Six samples were used and fixated in formalin 10%. Then samples were processed with paraffin method for HE stain. The results showed that parotid salivary glands of sumba ongole cattle were pure serous gland compared to mixed type (seromucous) in mandibular salivary glands. Parotid salivary glands acini of sumba ongole cattle consisted pyramid and cuboid cells. Pyramid acini consisted of pyramid cell, rounded nuclei and in center cell, eosinophilic sitoplasm, narrow lumen and had granules. Cuboid acini consisted of cuboid cell with nuclei in center cell, larger lumen, eosinophilic sitoplasm and had granules. Mandibular salivary glands acini of sumba ongole cattle consisted of serous acini, mucous acini and serous demillune. Serous acini consisted of pyramid cell, rounded nuclei in center cell, and eosinophilic sitoplasm. Mucous acini consisted of pyramid cell and had flattened nuclei in base cell. Serous demillune consisted of serous in peripher and mucous cells and seen to be crescent cell. Ducts system consisted of intercalated, striated and interlobular ducts. Interlobular ducts of parotid salivary glands had goblet cell while in mandibular glands not seen goblet cell.